Strategi Pemenangan Partai Golongan Karya Pada Pemilihan Kepala Daerah Kabupaten Seram Bagian Timur Tahun 2020 - Angar, Muhammad Nasir; Madubun, Jusuf; Tehuayo, Johan (Journal of Government Science Studies, 2022)
This study is a descriptive qualitative research that aims to know the winning strategy of the Golkar Party in the 2020 Seram Bagian Timur Regency Election. The study results showed that the realization of the Party's programs offered to the community is more inclined to the people's economy, such as in infrastructure, education, and health. The placement of figures was very influential in winning the 2020 Pilkada. The political behavior of the community tends to choose Mukti and Idris because of the candidate's character, vision, and mission on the collective expectations of the community. In the Adat leadership, Pak Mukti supports and develops local wisdom and inaugurates Adat leaders in Seram Bagian Timur Regency. Pak Mukti's leadership always tends to represent the interests of Adat.